2023
DOI: 10.1186/s12905-023-02365-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual-related determinants of life satisfaction among married women: A cross-sectional study

Abstract: Background and aim Life satisfaction refers to the perceived satisfaction of individuals concerning various aspects of their lives. The present study investigated the predictive role of sexual-related determinants in life satisfaction among married women. Methods A cross-sectional study was conducted from August to November 2021. A total of 350 married women with at least six months of cohabitation with husbands were included in the study. The stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(43 reference statements)
6
0
0
Order By: Relevance
“…Further, if practitioners see sexual difficulties in female survivors, they should address the possibility that these difficulties may be linked to mental health difficulties or rooted in relationship distress. This aligns with previous research suggesting that relationship distress significantly relates to sexual functioning in breast cancer survivors [44].…”
Section: Relationship and Sexual Factors And Psychological Well-beingsupporting
confidence: 91%
See 1 more Smart Citation
“…Further, if practitioners see sexual difficulties in female survivors, they should address the possibility that these difficulties may be linked to mental health difficulties or rooted in relationship distress. This aligns with previous research suggesting that relationship distress significantly relates to sexual functioning in breast cancer survivors [44].…”
Section: Relationship and Sexual Factors And Psychological Well-beingsupporting
confidence: 91%
“…Considering these results, female patients may benefit from all aspects of ACT while male clients may benefit from introducing value identification and goals related to those values early on in treatment. For females, sexual pleasure and orgasm were related to all three pillars of PF, supporting Bahrami et al [44], who reported that women's sexual arousal and satisfaction are closely tied to the quality of their relationship. This is important to note for clinicians working with female cancer patients; fostering PF may help to increase sexual pleasure and, in turn, improve relationship quality and satisfaction with life.…”
Section: Psychological Flexibility and Its Connection To Relationship...supporting
confidence: 67%
“…Further, if practitioners see sexual difficulties in female survivors, they should address the possibility that these difficulties may be linked to mental health difficulties or rooted in relationship distress. This aligns with previous research suggesting that relationship distress significantly relates to sexual functioning in breast cancer survivors [44].…”
Section: Relationship and Sexual Factors And Psychological Well-beingsupporting
confidence: 91%
“…Considering these results, female patients may benefit from all aspects of ACT while male clients may benefit from introducing value identification and goals related to those values early on in treatment. For females, sexual pleasure and orgasm were related to all three pillars of PF, supporting Bahrami et al [44], who reported that women's sexual arousal and satisfaction are closely tied to the quality of their relationship. This is important to note for clinicians working with female cancer patients; fostering PF may help to increase sexual pleasure and, in turn, improve relationship quality and satisfaction with life.…”
Section: Psychological Flexibility and Its Connection To Relationship...supporting
confidence: 67%
“…Considering these results, female patients may benefit from all aspects of ACT while male clients may benefit from introducing value identification and goals related to those values early on in treatment. For females, sexual pleasure and orgasm were related to all three pillars of PF, supporting Bahrami et al [44], who reported that women's sexual arousal and satisfaction are closely tied to the quality of their relationship. This is important to note for clinicians working with female cancer patients; fostering PF may help to increase sexual pleasure and, in turn, improve relationship quality and satisfaction with life.…”
Section: Psychological Flexibility and Its Connection To Relationship...supporting
confidence: 67%